Composite wire suitable for high-speed FDM 3D printing and preparation method
By using composite wires in high-speed FDM 3D printing, combined with polymer modified matrix, elastomer resin and ultrafine thermal conducting agent and other components, the problem of easy destruction and insufficient thermal conductivity of wires in high-speed printing is solved, and higher toughness, impact resistance and printing success rate are achieved.
Patent Information
- Application Number
- CN202510044157.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-11
- Publication Date
- 2025-03-25
AI Technical Summary
During high-speed FDM 3D printing, existing wires are prone to damage due to impact loads, and insufficient melt flow rate and thermal conductivity, resulting in unstable feeding and low printing quality.
Composite wire materials are used, and their compositions include polymer modified substrates, elastomeric resins, ultrafine thermal conductors, compatibility agents, toughening agents, nucleating agents, lubricants and antioxidants. The toughness, impact resistance and thermal conductivity of the wire materials are improved through specific preparation methods.
It improves the toughness and impact resistance of composite wires, ensures stable feeding under high-speed printing conditions (400~700 mm/s), avoids wire drawing and plugging, and improves printing success rate and molding accuracy.
Smart Images

Figure CN119684768A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to 3D printing, and in particular to a composite wire suitable for high-speed FDM 3D printing and a preparation method thereof. Background Art
[0002] Three-dimensional (3D) printing is also known as additive manufacturing. Different from subtractive manufacturing, it is an emerging manufacturing technology that uses digital models to stack materials layer by layer to make physical objects. 3D printing has the characteristics of high manufacturing efficiency, large design freedom, reduced material waste, support for small batch production and customized services, and is increasingly attracting widespread attention. At present, 3D printing technology has been applied to many fields, such as aerospace, national defense, automobiles, and biomedicine, and is gradually expanding to more other fields.
[0003] Fused deposition modeling (FDM) is one of the commonly used 3D printing methods. FDM printing uses rolled wire as raw material, which is transferred to the temperature-controlled nozzle head through a driving wheel and heated and melted. Then the nozzle is moved to the specified position according to the 3D model data to extrude the molten material and finally solidify it into shape. FDM technology has the advantages of low cost, wide material selection and high flexibility. In addition, in response to the shortcomings of slow FDM printing speed, a wave of high-speed FDM high-speed 3D printers has been set off worldwide in the past two years. Various manufacturers have launched high-speed machines. Through software and hardware technology innovations such as algorithms to improve printing speed and quality, the use of stronger and better hardware, and the application of AI technology, the FDM printing speed has been increased from the conventional 70~80mm / s to 5 to 10 times (400~700mm / s), and FDM printing has fully entered the high-speed era.
[0004] The wires used in FDM printing include polymer wires, metal wires, ceramic wires and other types. Among them, PLA, PETG, and PA6 are commonly used polymer matrix materials. They are easily damaged when subjected to impact loads, so they need to be toughened and impact-modified when processed into FDM wires. In addition, during high-speed FDM printing, in order to ensure smooth feeding, the melt flow rate of the wire needs to be effectively adjusted. Since the printing temperature needs to be increased during high-speed printing, it is also necessary to improve the thermal conductivity of the FDM printing wire, so that it is easier to cool down while achieving rapid heating and melting, meeting the needs of high-speed printing feeding and rapid cooling and shaping. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a composite wire suitable for high-speed FDM 3D printing; another purpose of the present invention is to provide a method for preparing a composite wire suitable for high-speed FDM 3D printing.
[0006] Technical solution: A composite wire suitable for high-speed FDM 3D printing, comprising the following components by weight: 70-90 parts of a polymer modified matrix, 3-20 parts of an elastomer resin, 1-15 parts of an ultrafine thermal conductor, 2-10 parts of a compatibilizer, 2-12 parts of a toughening agent, 0-2 parts of a nucleating agent, 0.2-5 parts of a lubricant, and 0.2-1 parts of an antioxidant;
[0007] The preparation method of the polymer modified matrix is as follows: adding cellulose to chloroform to dissolve, adding 2,2,6,6-tetramethylpiperidine-nitrogen-oxide (TMPEO) and NaBr under stirring, dropping NaClO at 0±5°C for oxidation reaction, washing and liquid separation after the reaction, adding anhydrous magnesium sulfate to the organic phase for drying, filtering the magnesium sulfate, and removing chloroform under reduced pressure to obtain nanocellulose, adding nanocellulose to chloroform to dissolve, adding PLA to dissolve under stirring, dropping triisooctyl citrate, stirring for 2 hours, and removing chloroform under reduced pressure to obtain the corresponding polymer modified matrix;
[0008] The ultrafine thermal conductor is prepared by adding nano copper oxide, ammonium chloride and EDTA to ethanol for heating and dissolving, adding nano magnesium powder, heating and mechanical stirring to carry out metal ion exchange reaction, and removing ethanol by evaporation under reduced pressure to obtain the ultrafine thermal conductor.
[0009] Preferably, the nanocellulose is nanocellulose in which the primary alcohol hydroxyl group at the C6 position of cellulose is oxidized to a carboxyl group without affecting the changes of functional groups at other carbon positions.
[0010] Preferably, the elastomeric resin is one of TPU, EVA, and TPEE, and has a melt flow rate of 1 to 15 g / 10 min (190 to 260° C., 2.16 kg).
[0011] Preferably, the compatibilizer is one or more of polylactic acid grafted with maleic anhydride, polypropylene grafted with maleic anhydride, isocyanate-terminated polyurethane prepolymer, and polystyrene grafted with oxazoline.
[0012] Preferably, the particle size of the ultrafine thermal conductor is 20-200 nm.
[0013] Preferably, the toughening agent is one or more of ethylene-methyl acrylate copolymer, sarling ionomer resin, and terminal hydroxyl hyperbranched polyester.
[0014] Preferably, the nucleating agent is one or more of nano titanium dioxide, nano mica, di[4-tert-butylbenzoate]aluminum hydroxide, and dibenzylidene sorbitol.
[0015] Preferably, the lubricant is one or more of polyethylene wax, solid paraffin, ethylene bis stearamide, oleic acid amide, and pentaerythritol stearate.
[0016] Preferably, the antioxidant is one or more of antioxidant 1010, antioxidant 168, and antioxidant 1076.
[0017] A method for preparing a composite wire suitable for high-speed FDM 3D printing comprises the following steps:
[0018] S1. Add toughening agent, ultrafine thermal conductor, lubricant and antioxidant into an internal mixer and mix at 95-150° C. for 10-20 min, and obtain thermal conductive toughening masterbatch after granulation;
[0019] S2, drying the polymer modified matrix and the elastomer resin at 70-90° C. and 75-100° C. respectively, and then adding them and the thermal conductive toughening masterbatch, compatibilizer, nucleating agent and lubricant in step S1 into a high-speed mixer and mixing for 15 minutes to obtain a premix;
[0020] S3, adding the premix in step S2 into a twin-screw, extruding and granulating at 175-240° C. to obtain modified particles, and then drying and extruding using a single-screw extruder at 185-250° C. to produce high-speed FDM 3D printing filaments.
[0021] Beneficial effects:
[0022] (1) The present invention adds oxidized nanocellulose and tri-ethylhexyl citrate to PLA to enhance the plasticizing effect, thereby increasing the degradation rate of PLA / EC and reducing the degree of environmental pollution.
[0023] (2) TPU, EVA and TPEE in the present invention are all thermoplastic elastomer materials, which are the abbreviations of thermoplastic polyurethane, ethylene-vinyl acetate copolymer and thermoplastic polyester elastomer respectively. Mixing them with a polymer modified matrix can improve the toughness and impact resistance of the matrix material. In addition, adding a compatibilizer, a nucleating agent, a toughening agent and an inorganic thermal conductor to the polymer modified matrix can improve the interface characteristics and crystallization properties of the composite wire, and further improve the toughness and impact resistance of the wire and its products under the synergistic effect.
[0024] (3) The present invention can adjust the melt fluidity of the wire to an appropriate range by adding a thermoplastic elastomer and reactive compatibilizers such as grafted maleic anhydride, polyurethane prepolymer, and grafted oxazoline to the polymer modified matrix, thereby ensuring effective material feeding during high-speed 3D printing while preventing a large range of viscosity reduction. The wire can be suitable for 400-700 mm / s high-speed FDM 3D printing, and no wire drawing, plugging, or detachment from the base plate will occur during printing.
[0025] (4) The present invention adopts ultrafine thermal conductive agent as wire filler, and the thermal conductivity and antioxidant properties of the prepared composite wire are significantly improved, which can promote the rapid melting of 3D consumables and accelerate the cooling speed. While ensuring stable feeding, it can also achieve rapid shaping, which can improve the printing success rate and molding accuracy under high-speed printing conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a performance and printing effect comparison diagram of the embodiment and the comparative example. DETAILED DESCRIPTION
[0027] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0028] Example 1
[0029] A PLA composite wire suitable for high-speed FDM 3D printing, the composite wire is obtained by the following preparation method:
[0030] (1) Preparation of polymer modified matrix: 100 g of cellulose was added to a reaction bottle, 1000 g of chloroform was added to dissolve, 2 g of TMPEO and 10 g of NaBr were added under stirring, 280 g of NaClO was added dropwise at 0±5°C for oxidation reaction, washing and separation were performed after the reaction, anhydrous magnesium sulfate was added to the organic phase for drying, magnesium sulfate was filtered, chloroform was evaporated under reduced pressure to obtain nanocellulose, 5000 g of chloroform was added to the nanocellulose for dissolution, 950 g of PLA was added under stirring for dissolution, 50 g of triisooctyl citrate was added dropwise, stirring was performed for 2 h, and chloroform was evaporated under reduced pressure to obtain the corresponding polymer modified matrix;
[0031] (2) Preparation of ultrafine thermal conductor: Add 30g of nano copper oxide, 5g of ammonium chloride and 25g of EDTA into a reaction bottle, add ethanol and heat to dissolve, then add 38g of nano magnesium powder, keep the temperature at 60℃ and stir to react for 2h, and evaporate the ethanol under reduced pressure at -0.09MPa to obtain the corresponding ultrafine thermal conductor;
[0032] (3) Add 60g of toughening agent ethylene-methyl acrylate copolymer, 36g of ultrafine thermal conductor in step (2), 3g of lubricant oleic acid amide, and 3.5g of antioxidant 1010 into an internal mixer and mix at 140°C for 15min to obtain a thermal conductive toughening masterbatch after granulation;
[0033] (4) Dry 400 g of the polymer modified matrix and 75 g of the elastomer resin TPEE in step (1) at 80° C. and 75° C., respectively, and then add them, 40 g of the thermal conductive toughening masterbatch in step S3, 18 g of the compatibilizer polypropylene grafted maleic anhydride, 6 g of the nucleating agent nano titanium dioxide, and 3 g of the lubricant oleic acid amide into a high-speed mixer and mix for 15 minutes to obtain a premix;
[0034] (5) Add the premix in step (4) into a twin-screw extruder, extrude and granulate at 175°C to obtain modified particles, and then use a single-screw extruder to extrude at 185°C to produce high-speed FDM 3D printing filaments after drying.
[0035] Example 2
[0036] A PETG composite wire suitable for high-speed FDM 3D printing, the composite wire is obtained by the following preparation method:
[0037] (1) Preparation of polymer modified matrix: 100 g of cellulose was added to a reaction bottle, 1000 g of chloroform was added to dissolve, 2 g of TMPEO and 10 g of NaBr were added under stirring, 280 g of NaClO was added dropwise at 0±5°C for oxidation reaction, washing and separation were performed after the reaction, anhydrous magnesium sulfate was added to the organic phase for drying, magnesium sulfate was filtered, chloroform was evaporated under reduced pressure to obtain nanocellulose, 5000 g of chloroform was added to the nanocellulose for dissolution, 950 g of PLA was added under stirring for dissolution, 50 g of triisooctyl citrate was added dropwise, stirring was performed for 2 h, and chloroform was evaporated under reduced pressure to obtain the corresponding polymer modified matrix;
[0038] (2) Preparation of ultrafine thermal conductor: Add 30g of nano copper oxide, 5g of ammonium chloride and 25g of EDTA into a reaction bottle, add ethanol and heat to dissolve, then add 38g of nano magnesium powder, keep the temperature at 60℃ and stir to react for 2h, and evaporate the ethanol under reduced pressure at -0.09MPa to obtain the corresponding ultrafine thermal conductor;
[0039] (3) Add 55 g of toughening agent terminal hydroxyl hyperbranched polyester, 60 g of the ultrafine thermal conductor in step (2), 2 g of lubricant pentaerythritol stearate, and 3.5 g of antioxidant 1010 into an internal mixer and knead at 95° C. for 15 min. After granulation, a thermal conductive toughening masterbatch is obtained;
[0040] (4) 450 g of the polymer modified matrix and 50 g of the elastomer resin TPU in step (1) were dried at 70° C. and 90° C., respectively, and then added to a high-speed mixer and mixed for 20 min with 48 g of the thermal conductive toughening masterbatch in step S3, 42 g of the compatibilizer polystyrene grafted oxazoline, 5 g of the nucleating agent di[4-tert-butylbenzoic acid] aluminum hydroxide, and 2.5 g of the lubricant pentaerythritol stearate to obtain a premix;
[0041] (5) Add the premix in step (4) into a twin-screw extruder, extrude and granulate at 220°C to obtain modified particles, and then use a single-screw extruder at 230°C to extrude the particles to produce high-speed FDM 3D printing filaments after drying.
[0042] Example 3
[0043] A PA6 composite wire suitable for high-speed FDM 3D printing, the composite wire is obtained by the following preparation method:
[0044] (1) Preparation of polymer modified matrix: 100 g of cellulose was added to a reaction bottle, 1000 g of chloroform was added to dissolve, 2 g of TMPEO and 10 g of NaBr were added under stirring, 280 g of NaClO was added dropwise at 0±5°C for oxidation reaction, washing and separation were performed after the reaction, anhydrous magnesium sulfate was added to the organic phase for drying, magnesium sulfate was filtered, chloroform was evaporated under reduced pressure to obtain nanocellulose, 5000 g of chloroform was added to the nanocellulose for dissolution, 950 g of PLA was added under stirring for dissolution, 50 g of triisooctyl citrate was added dropwise, stirring was performed for 2 h, and chloroform was evaporated under reduced pressure to obtain the corresponding polymer modified matrix;
[0045] (2) Preparation of ultrafine thermal conductor: Add 30g of nano copper oxide, 5g of ammonium chloride and 25g of EDTA into a reaction bottle, add ethanol and heat to dissolve, then add 38g of nano magnesium powder, keep the temperature at 60℃ and stir to react for 2h, and evaporate the ethanol under reduced pressure at -0.09MPa to obtain the corresponding ultrafine thermal conductor;
[0046] (3) Add 50 g of toughening agent terminal hydroxyl hyperbranched polyester, 50 g of the ultrafine thermal conductor in step (2), 4.5 g of lubricant ethylene bisstearamide, 1 g of antioxidant 1010, and 3 g of antioxidant 1076 into an internal mixer and mix at 100° C. for 15 min. After granulation, a thermal conductive toughening masterbatch is obtained;
[0047] (4) Dry 450 g of the polymer modified matrix and 50 g of the elastomer resin EVA in step (1) at 90° C. and 100° C., respectively, and then add them, 35 g of the thermal conductive toughening masterbatch in step S3, 32 g of the compatibilizer polypropylene grafted maleic anhydride, 6 g of the nucleating agent dibenzylidene sorbitol, and 1.5 g of the lubricant ethylene bis stearamide into a high-speed mixer and mix for 20 min to obtain a premix;
[0048] (5) Add the premix in step (4) into a twin-screw extruder, extrude and granulate at 240°C to obtain modified particles, and then use a single-screw extruder at 250°C to extrude the particles to produce high-speed FDM 3D printing filaments after drying.
[0049] Comparative Example 1
[0050] A PLA filament suitable for high-speed FDM 3D printing, the composite filament is obtained by the following preparation method:
[0051] (1) PLA 450 g was dried at 90°C, and then added to a high-speed mixer with 32 g of a compatibilizer, polylactic acid grafted maleic anhydride, 5 g of a nucleating agent, di[4-tert-butylbenzoic acid] aluminum hydroxide, 2.5 g of a lubricant, pentaerythritol stearate, and 4 g of an antioxidant 1076, and mixed for 15 min to obtain a premix;
[0052] (2) Add the premix in step (1) into a twin-screw extruder, extrude and granulate at 210°C to obtain modified particles, and then use a single-screw extruder at 210°C to extrude the particles into wires after drying.
[0053] Comparative Example 2
[0054] A PETG composite wire suitable for high-speed FDM 3D printing, the composite wire is obtained by the following preparation method:
[0055] (1) Preparation of polymer modified matrix: 100 g of cellulose was added to a reaction bottle, 1000 g of chloroform was added to dissolve, 2 g of TMPEO and 10 g of NaBr were added under stirring, 280 g of NaClO was added dropwise at 0±5°C for oxidation reaction, washing and separation were performed after the reaction, anhydrous magnesium sulfate was added to the organic phase for drying, magnesium sulfate was filtered, chloroform was evaporated under reduced pressure to obtain nanocellulose, 5000 g of chloroform was added to the nanocellulose for dissolution, 950 g of PLA was added under stirring for dissolution, 50 g of triisooctyl citrate was added dropwise, stirring was performed for 2 h, and chloroform was evaporated under reduced pressure to obtain the corresponding polymer modified matrix;
[0056] (2) Add 55 g of toughening agent terminal hydroxyl hyperbranched polyester, 2 g of lubricant pentaerythritol stearate, and 3.5 g of antioxidant 1010 into an internal mixer and mix at 110° C. for 15 min. After granulation, a toughening masterbatch is obtained;
[0057] (3) 450 g of the polymer modified matrix and 50 g of the elastomer resin TPU in step (1) were dried at 70° C. and 90° C., respectively, and then added to a high-speed mixer and mixed with 48 g of the thermal conductive toughening masterbatch in step S3, 5 g of the nucleating agent di[4-tert-butylbenzoic acid] aluminum hydroxide, and 2.5 g of the lubricant pentaerythritol stearate for 20 min to obtain a premix;
[0058] (4) Add the premix in step (3) into a twin-screw extruder, extrude and granulate at 220°C to obtain modified particles, and then use a single-screw extruder at 230°C to extrude the particles into wires after drying.
[0059] Comparative Example 3
[0060] A PA6 composite wire suitable for high-speed FDM 3D printing, the composite wire is obtained by the following preparation method:
[0061] (1) Preparation of polymer modified matrix: 100 g of cellulose was added to a reaction bottle, 1000 g of chloroform was added to dissolve, 2 g of TMPEO and 10 g of NaBr were added under stirring, 280 g of NaClO was added dropwise at 0±5°C for oxidation reaction, washing and separation were performed after the reaction, anhydrous magnesium sulfate was added to the organic phase for drying, magnesium sulfate was filtered, chloroform was evaporated under reduced pressure to obtain nanocellulose, 5000 g of chloroform was added to the nanocellulose for dissolution, 950 g of PLA was added under stirring for dissolution, 50 g of triisooctyl citrate was added dropwise, stirring was performed for 2 h, and chloroform was evaporated under reduced pressure to obtain the corresponding polymer modified matrix;
[0062] (2) Add 55 g of toughening agent terminal hydroxyl hyperbranched polyester, 2 g of lubricant pentaerythritol stearate, and 3.5 g of antioxidant 1010 into an internal mixer and mix at 95°C for 15 min. After granulation, a toughening masterbatch is obtained.
[0063] (3) 450 g of the polymer modified matrix and 50 g of the elastomer resin TPU in step (1) were dried at 70° C. and 90° C., respectively, and then added to a high-speed mixer and mixed for 20 min with 48 g of the thermal conductive toughening masterbatch in step S3, 42 g of the compatibilizer polystyrene grafted oxazoline, 5 g of the nucleating agent di[4-tert-butylbenzoic acid] aluminum hydroxide, and 2.5 g of the lubricant pentaerythritol stearate to obtain a premix;
[0064] (4) Add the premix in step (3) into a twin-screw extruder, extrude and granulate at 220°C to obtain modified particles, and then use a single-screw extruder at 230°C to extrude the particles into wires after drying.
[0065] The composition and preparation process of the FDM wires described in Examples 1, 2, and 3 correspond to those in Comparative Examples 1, 2, and 3, respectively, and the composition formulas and preparation methods thereof are basically the same. The main differences are as follows: (1) In Comparative Example 1, the polymer modified matrix is PLA, and no TPEE elastomer, ultrafine thermal conductor, or toughening agent is added, and no thermal conductive toughening masterbatch is prepared; (2) In Comparative Example 2, no ultrafine thermal conductor or compatibilizer is added; and (3) In Comparative Example 3, no ultrafine thermal conductor is added.
[0066] Test Case
[0067] Mechanical properties: Refer to GB / T 1040, GB / T 9341, GB / T1043 standards to test the tensile strength σ of the composite wire printing sample t , bending strength σ b , notched impact strength I.
[0068] Thermal conductivity: Use a laser thermal conductivity meter to determine the thermal diffusion coefficient α of the composite wire, and use DSC to test the specific heat capacity C P , the density ρ is determined by the drainage method, and then according to the formula λ=α ×C P×ρ to calculate the thermal conductivity λ of the wire.
[0069] Melt fluidity: The FDM wire was cut into pellets, and the melt flow rate (MFR) was measured using the method specified in GB / T 3682-2000 (190-260°C, 2.16 kg).
[0070] Printing effect: Under high-speed printing conditions (400-700 mm / s), the FDM composite wire is made into a solid model, and the appearance of the product is observed to confirm whether there is wire drawing, plugging, and detachment from the base plate.
[0071] The performance and printing effect comparison results of the above embodiments and comparative examples are as follows: Figure 1 As shown. The results show that the composite wire provided by the present invention for high-speed FDM 3D printing has excellent mechanical properties and is particularly suitable for printing at a high-speed printing speed of 400~700 mm / s. It can be seen from Examples 1~3 and Comparative Examples 1~3 that (1) the modified polymer matrix, the addition of elastomers, compatibilizers, toughening agents, nucleating agents, and ultrafine thermal conductors improve the mechanical properties of the composite wire and its printed parts through synergistic interactions, especially the toughness and impact resistance are greatly enhanced; (2) In addition, the addition of elastomers and toughening agents can also adjust the melt flow rate of the wire to ensure rapid feeding and prevent serious wire drawing and printer nozzle clogging; (3) The addition of ultrafine high thermal conductivity components can improve the thermal conductivity of the composite wire, achieve rapid melting of the material and accelerate the cooling rate, which is conducive to obtaining a higher printing success rate and molding accuracy.
[0072] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A composite wire suitable for high-speed FDM 3D printing, characterized in that: The invention comprises the following components in parts by weight: 70-90 parts of polymer modified matrix, 3-20 parts of elastomer resin, 1-15 parts of ultrafine thermal conductor, 2-10 parts of compatibilizer, 2-12 parts of toughening agent, 0-2 parts of nucleating agent, 0.2-5 parts of lubricant, and 0.2-1 parts of antioxidant; The preparation method of the polymer modified matrix is as follows: adding cellulose to chloroform to dissolve, adding 2,2,6,6-tetramethylpiperidine-nitrogen-oxide (TMPEO) and NaBr under stirring, dropping NaClO at 0±5°C for oxidation reaction, washing and liquid separation after the reaction, adding anhydrous magnesium sulfate to the organic phase for drying, filtering the magnesium sulfate, and removing chloroform under reduced pressure to obtain nanocellulose, adding nanocellulose to chloroform to dissolve, adding PLA to dissolve under stirring, dropping triisooctyl citrate, stirring for 2 hours, and removing chloroform under reduced pressure to obtain the corresponding polymer modified matrix; The ultrafine thermal conductor is prepared by adding nano copper oxide, ammonium chloride and EDTA to ethanol for heating and dissolving, adding nano magnesium powder, heating and mechanical stirring to carry out metal ion exchange reaction, and removing ethanol by evaporation under reduced pressure to obtain the ultrafine thermal conductor.
2. The composite wire suitable for high-speed FDM 3D printing according to claim 1, characterized in that: Nanocellulose is a nanocellulose in which the primary alcohol hydroxyl group at the C6 position of cellulose is oxidized to a carboxyl group without affecting the changes of functional groups at other carbon positions.
3. The composite wire suitable for high-speed FDM 3D printing according to claim 1, characterized in that: The elastomer resin is one of TPU, EVA, and TPEE, and has a melt flow rate of 1 to 15 g / 10 min.
4. The composite wire suitable for high-speed FDM 3D printing according to claim 1, characterized in that: The compatibilizer is one or more of polylactic acid grafted with maleic anhydride, polypropylene grafted with maleic anhydride, isocyanate-terminated polyurethane prepolymer, and polystyrene grafted with oxazoline.
5. The composite wire suitable for high-speed FDM 3D printing according to claim 1, characterized in that: The particle size of ultrafine thermal conductor is 20~200nm.
6. The composite wire suitable for high-speed FDM 3D printing according to claim 1, characterized in that: The toughening agent is one or more of ethylene-methyl acrylate copolymer, sarling ionomer resin and terminal hydroxyl hyperbranched polyester.
7. The composite wire suitable for high-speed FDM 3D printing according to claim 1, characterized in that: The nucleating agent is one or more of nano titanium dioxide, nano mica, di[4-tert-butylbenzoic acid] aluminum hydroxide and dibenzylidene sorbitol.
8. The composite wire suitable for high-speed FDM 3D printing according to claim 1, characterized in that: The lubricant is one or more of polyethylene wax, solid paraffin, ethylene bis stearamide, oleic acid amide, and pentaerythritol stearate.
9. The composite wire suitable for high-speed FDM 3D printing according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 168, and antioxidant 1076.
10. A method for preparing a composite wire suitable for high-speed FDM 3D printing as claimed in claim 1, characterized in that: The following steps are involved: S1. Add toughening agent, ultrafine thermal conductor, lubricant and antioxidant into an internal mixer and mix at 95-150° C. for 10-20 min, and obtain thermal conductive toughening masterbatch after granulation; S2, drying the polymer modified matrix and the elastomer resin at 70-90° C. and 75-100° C. respectively, and then adding them and the thermal conductive toughening masterbatch, compatibilizer, nucleating agent and lubricant in step S1 into a high-speed mixer and mixing for 15 minutes to obtain a premix; S3, adding the premix in step S2 into a twin-screw, extruding and granulating at 175-240° C. to obtain modified particles, and then drying and extruding using a single-screw extruder at 185-250° C. to produce high-speed FDM 3D printing filaments.
Citation Information
Patent Citations
Toughened polylactic acid 3D printing material and preparation method thereof
CN107674392A
Composite wire suitable for heat conduction type rapid FDM 3D printing and preparation method
CN118562268A
Material for 3D printing, process for preparing the same and article thereof
US20170253681A1